The Digital Transformation of the Automotive Industry Catalysts, Roadmap, Practice - Winkelhake, Uwe.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Building on his decades of experience as a consultant and project manager in the automotive industry, the author develops comprehensive and pragmatic recommendations for action regarding the digital transformation of the automotive and supplier industries. At the heart is the transition from a vehicle-focused to a mobility-oriented business model. Based on the catalysts of the digital change, four digitisation fields are structured, and a roadmap for their transformation is presented. The topics of comprehensive change in corporate culture and an agile and efficient information technology are covered in detail as vital success factors. Selected practical examples of innovative digitisation projects provide additional ideas and impulses. An outlook on the automotive industry in the year 2040 completes the discourse.
Objective and scope of the book -- Development of information technology as catalyst of digitization -- "Digital lifestyle" of future employees and customers -- Technologies for digitization solutions -- Vision of digitized automotive industry 2030 -- Roadmap to sustainable digitization -- Company culture and organisation -- Information technology as enabler of digitization -- Examples of innovative digitization projects in the automotive industry -- Car Mobility 2040.
Keywords: Automotive engineering; Computer networks .; Industrial Management; Business information services; Automobile industry and trade; Automotive Engineering; Computer Communication Networks; Industrial Management; IT in Business; Automotive Industry